Pengaruh Stres Kerja Dan Motivasi Terhadap Kinerja Karyawan(Studi Pada Bank Jateng Syariah Cabang Surakarta) - Aziz, Umi Utaminingsih, Soepatini, S.E., M.Si., Ph.D (2016)
This study aimed to analyze the effect of work stress variables and motivation on employee performance Bank Syariah Branch Surakarta Central Java. In addition, this study also aims to analyze the significance of the dependent variables in explaining the performance of the employee. This type of research is quantitative research which is done on the employees of Bank Syariah Branch Surakarta Central Java. The population in this study were all employees at Bank Syariah Branch Surakarta Central Java as many as 50 people by the method of determination of the sample is census. The types and sources of data used in this study are primary data. Research data collection techniques through a questionnaire with Likert scale. Data were analyzed using the validity test, reliability test, classic assumption test (normality test, multicollinearity test, and eroscedasticity test), as well as multiple linear regression analysis (t-test, F, and test the coefficient of determination). Based on the results of multiple regression analysis showed that job stress negatively affects the performance of employees of Bank Syariah Branch Surakarta Central Java with t_count value of - 1.072 with 0.289 significance greater than 0.05. Motivation positive influence on employee performance Bank Syariah Branch Surakarta Central Java with t_count value of 4.489 with 0.000 significance of less than 0.05.